COP30 Joint Statement on Biological Solutions for Climate-Resilient Agriculture - Department of Agriculture, Livestock and Food Supply (MAPA) – Brazil; Embrapa; CGIAR (2025)
In this COP30 Joint Statement, Governments, led by Brazil's Department of Agriculture, Livestock and Food Supply (MAPA), Embrapa, and CGIAR, are urged to increase investment in biosolutions, establish coordination mechanisms, and create dedicated financing windows while streamlining science-based approval processes. Multilateral institutions and the private sector are invited to create blended finance facilities to de-risk investment and engage farmers through cooperative models and equitable value chains. The partners commit to co-creating solutions through multi-stakeholder dialogue and scaling proven innovations like biological nitrogen fixation and quality-assured bioinoculant networks.